An evaluation of abnormal puerperium - Jeenwal, Aarti; Jharbade, Hemlata; Singh, Nishita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Puerperium is strictly defined as the period of confinement during and just after birth. It is the period following childbirth during which body tissues specially the genital organ reverts back approximately to the pre-pregnant state both anatomically and physiologically. At some stages some of these well-orchestrated changes can go away resulting in complications which can endanger life. Methods: Retrospective c study was conducted in Department of Obstetrics and Gynecology of M.G.M. Medical College and M. Y. Hospitals, Indore. The cases were selected randomly from the patient who were admitted in M.Y. Hospital who had either a vaginal or caesarean delivery (both in our institution as well as outside institution) during the study period, irrespective of age, parity and registration status. Data was recorded in predesigned coded case report forms and statistical analysis was performed. Results: Authors found that puerperal pyrexia was the most common complication, accounting for 38.96% of total cases. The second most common complication was perineal pain affecting 28.15% of cases. The other complication was wound gaping/discharge (11.71%), mastitis and breast abscess (6.81%), secondary postpartum hemorrhage (5.33%), episiotomy gaping and infection (4%), perineal hematoma (0.59%), wound dehiscence (0.3%) and other rare causes accounted for 4.15% of the complication. Conclusions: Puerperal period is as important as antenatal period. Anaemia, suboptimal personal hygiene as well as improper sterilization can resulted in severe health hazards such as septicemia, disseminated intravascular coagulation as well as death. So, risk factor should be treated vigorously.